April 2022 Update to the Global Database of Shared Prosperity : What’s New - Sabatino, Carlos (World Bank, Washington, DC, 2022)
The April 2022 update introduces the 9th edition of the Global Database of Shared Prosperity. Shared prosperity, defined as the growth in household per capita income or consumption of the poorest 40 percent of the population, is the World Bank’s second Twin Goal, alongside ending extreme poverty. The Global Database of Shared Prosperity (GDSP) is the database that is used to monitor the progress of this indicator. This technical note describes the GDSP, documents the available data in this edition, and highlights the main differences with the 8th edition.